STRATEGI PENGEMBANGAN USAHA KOPI EXCELSA DI KECAMATAN WONOSALAM KABUPATEN JOMBANG MENGGUNAKAN BISNIS MODEL CANVAS - Hariri, Rifan; Harini, Noor; Sutawi, Sutawi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Excelsa coffee in Wonosalam Subdistrict in terms of profit is still not equal to Arabica and Robusta coffee so there needs to be a development strategy. The purpose of this research is to formulate a business development strategy for Excelsa coffee in Wonosalam Subdistrict. This research uses qualitative research. The sampling technique used was snowball sampling. In the snowball sampling technique, informants gave recommendations to the researchers to interview other informants who understood more about Excelsa coffee in Wonosalam Subdistrict. The results obtained show that the development of Excelsa coffee business in Wonosalam Subdistrict can be done by collaborating with hotels, restaurants, cafes and the local tourism industry, using social media to interact with customers, marketing without going through middlemen, targeting the lower middle class segment of society and there also needs to be another source of income in the form of using coffee plantations as agro-tourism and selling coffee derivative products.